Comparison of post partum sequalae between mothers undergoing vaginal delivery and caesarian section. - Fernando, M.M.P (My University, 2003)
The present study was planned with the objectives of describing postpartum health problems during the puerperium and to compare these problems between those undergoing vaginal delivery and caesarian section. this study that all mothers especially those who undergo vaginal delivery, should be assessed at least once following delivery for identification and appropriate management of squeal, which may need medical intervention